FUTEVÔLEI ON THE BEACH OF COPACABANA AND ITS CULTURAL IDENTITY (Fiep Bulletin - online, 2014)
Among the sportive practice in free space, specially on the sand of the beach, we may find "futevôlei"- a mixture between soccer and volleyball. This sport was created in Rio de Janeiro, during the 60's, between 1964 and 1965, by a group of contesting guys, having as a leader an ex- soccer player from the Botafogo Club of soccer and Regatas-Otávio as he was named. These people innovate facing a crisis, they appropriated models they have already had (soccer and volley). They rebuild the daily life, making usage of what Michel de Certeau (1999) called tactic, a movement which is animated by one doing the practice, creating his own way to do it, alternating everything that was prescribed. A calculated action, as condition of autonomy. The futevôlei is presented as a way of leisure and its practitioners ,  in the sense that id developed in the free space of people, that is, not connected  with work and studies.Its male identity and on the beach makes it stronger in a free zone, the beach, a space that Archetti (2003) considers proper to the beginnings of the  hybrid, sexuality and also to the  exhibition of bodies. In the case, an intentional hybrid, seen as positive, representing creativity, vitality and strength. The Copacabana beach, place of origin of the sport, is seen by the practitioners as a perfect place, where cause and consequence (Maffesoli 2004) is the communion -communication. The beach makes a link, it makes a place of celebration, an emblematic place, where mysteries are celebrated, where the guys "futebolistas" meet each other, know each other, and by the sharing of affection and common emotions, know themselves, their limits and potentialities. It is a kind of altar nowadays, a space of sociality linked by a cultural futevôlei.